CYP11B1 gene polymorphisms and susceptibility to ischemic stroke in a Chinese Han population - Liu, Gaowen; Duan, Ying (Frontiers in Neuroscience, 2022)
Objectives Ischemic stroke (IS) is the major cause of death and disability. While previous studies confirmed that CYP11B1 is closely associated with IS, the present study aimed to analyze the impact of CYP11B1 gene polymorphisms on the IS susceptibility. Methods The present study genotyped six single nucleotide polymorphisms (SNPs) (including rs4736312, rs5017238, rs5301, rs5283, rs6410, and rs4534) of CYP11B1 in peripheral blood samples from IS and control populations. Logistic regression analysis was used to analyze the association between the SNPs and IS risk. The multifactor dimensionality reduction (MDR) method was used to determine the roles of SNP–SNP interactions in IS. Results The present study showed that rs5283 was associated with an increased susceptibility to IS [odds ratio (OR) 1.81, p = 0.012]. On the contrary, rs6410 had a protective influence on IS risk (OR 0.56, p = 0.020). Stratified analyses indicated that rs5283 could enhance the risk of IS in subjects aged >63 years (OR 2.41, p = 0.011), of female gender (OR 3.31, p = 0.001), that do not smoke (OR 1.64, p = 0.005), and with hypertension (OR 2.07, p = 0.003). Whereas, rs6410 was related to a lower susceptibility to IS in subjects aged >63 years (OR 0.43, p = 0.032), of female gender (OR 0.30, p = 0.006), do not smoke (OR 0.42, p = 0.017), and with hypertension (OR 0.52, p = 0.022). Besides, rs4736312 reduced the IS susceptibility in non-smokers (OR 0.69, p = 0.031). Rs4534 had a risk-decreasing impact on IS in non-drinking (OR 0.54, p = 0.016). Moreover, the results of the MDR analysis corroborate that the best prediction model for IS was rs5283. Conclusion This study revealed that CYP11B1 gene polymorphisms strongly correlated with IS in the Chinese Han population.